Comparative Analysis of Patient Safety Culture Among Trained and Untrained Staff at the Educational Dental and Oral Hospital in Semarang: Cross-Sectional Study - Retno Kusniati; Etny Dyah Harniati; Yasinia Annisa Purbomurti (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Patient safety (PS) is crucial to healthcare services, including in dental practice. A good patient safety culture can reduce adverse events and improve the quality of care. Patient safety training is one strategy to improve safety culture. However, there are still gaps in the implementation of patient safety culture (PSC). This study aims to analyze the differences in patient safety culture between staff who have received patient safety training and those who have not. Methods: This study was cross-sectional using the Hospital Survey on Patient Safety Culture (HSOPSC) questionnaire. Participants were staff at the Dental and Oral Hospital of the University of Muhammadiyah Semarang who met the inclusion criteria. Data were collected for two weeks, and statistical analysis was performed using the Mann-Whitney test to compare differences in patient safety culture between groups that had received training and those that had not. Results: Of the 12 dimensions of patient safety culture, teamwork within the unit (89.6 %) and organizational learning–continuous improvement (85.8%) had the highest positive response rates. In contrast, the dimensions of staffing (35.4 % ) and openness of communication (36.2%) recorded the lowest positive responses. Staff who had attended patient safety training showed a higher positive response than those who had not, but the results of the difference in mean scores with 95% confidence intervals (CI) proved to be statistically insignificant (p = 0.563). Conclusion: Patient safety training increased the perception of safety culture, although there was no significant difference in scores between staff who had and had not attended training. A supportive work environment and good teamwork are essential in shaping a patient safety culture. Hospitals should consider strategies to increase staffing so that they are not working in “crisis mode” to maintain patient safety and to support the Indonesian Ministry of Health and WHO Patient Safety Action Plan.